A novel, solar panel-based screenwashing apparatus for the bulk collection of microvertebrate fossils in the field - Woodruff, Cary; Hart, William; Colesmith, Alex; Kreider , Danny; Austin, Gianna; Bounassi, Alexander; Woodruff, Hunter (Vertebrate Anatomy Morphology Palaeontology, 2025)
The contribution of microvertebrate fossils towards various paleobiological and geochemical studies are becoming increasingly more numerous and significant. As such, several methods have been developed for the extraction and collection of microfossils from bulk sediment. In the field, screenwashing relies on a sieve in a fluvial setting to passively wet sieve the fossiliferous sediment. Sampling in the field can be much easier as it alleviates the need to transport a large quantity of bulk sediment back to the home institution. However, the primary concerns of sampling bulk matrix in the field are access to a fluvial amenity and availability of sediment that can be successfully wet sieved. We encountered both issues at a locality where: 1) there was no access to any sort of fluvial feature, and 2) even with a man-made water containing feature, the clay-rich sediment at this locality created an impermeable layer in each screen box that clogged the screen, and prevented wet sieving. To overcome these challenges, we designed and implemented a two-part apparatus onsite in the field that relied on a solar-powered water transfer pump to cycle water throughout a system to provide fluvial agitation; whereby preventing the buildup of an impermeable clay layer, and allowing the processing and collection of microvertebrate material from this locality in the field. While there are numerous protocols and methodologies for the processing of microvertebrate material, the methodology we document in this study highlights another technique that can be utilized, and will hopefully prove useful to others encountering similar difficulties.